2012
DOI: 10.1088/1741-2560/9/2/026028
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying long-term microelectrode array functionality using chronicin vivoimpedance testing

Abstract: Long-term acquisition of high-quality neural recordings is a cornerstone of neuroprosthetic system design. Mitigating the experimental variability of chronically implanted arrays has been a formidable task because the sensor recording sites can be influenced by biotic and abiotic responses. Several studies have implicated changes in electrical interface impedance as a preliminary marker to infer electrode viability. Microelectrode impedance plays an important role in the monitoring of low amplitude and high-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
165
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(181 citation statements)
references
References 49 publications
15
165
1
Order By: Relevance
“…In vitro impedance measurements were made using the EVAL-AD5934EBZ (Analog Devices, MA, USA) using the potentiostatic method [14].…”
Section: Impedence Spectroscopymentioning
confidence: 99%
“…In vitro impedance measurements were made using the EVAL-AD5934EBZ (Analog Devices, MA, USA) using the potentiostatic method [14].…”
Section: Impedence Spectroscopymentioning
confidence: 99%
“…The spinal cord is highly viscoelastic (elastic modulus of 0.5-1 MPa) and experiences up to ~10% of repeated strain during motion [25,26] , presenting a challenge to combined intraspinal neural recording and optical stimulation, since the majority of neural probes and light-delivery devices are comprised of brittle materials [27][28][29] that may cause damage to the neural tissue and fail under repeated deformation [30] . To overcome these limitations, we engineered highly flexible biomimetic all-polymer fiber probes that combine an optical core for optogenetic stimulation and conductive electrodes for simultaneous neural recording.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the size of the electrode surface and the impedance is inversely proportional, with electrodes with larger area exhibiting lower impedance (Butson et al, 2006;Ludwig et al, 2006). Prasad et al found that the ideal resistance for SUA detection is between 40-150kΩ (Prasad and Sanchez, 2012). : A: black dots: average extracellular spike amplitude (±SE) vs. tetrode tip distance from 19 labeled pyramidal cells.…”
Section: Sensors Recording Neuronal Activitymentioning
confidence: 99%
“…This leads to decreasing neuronal signal quality and SNR (Ludwig et al, 2006;Plenk, 2011;Wang et al, 2005). The microelectrode impedance fluctuates (Ward et al, 2009) and increases over time after contacting the biological tissue (Prasad and Sanchez, 2012). There are studies however, demonstrating long term biocompatibility of microelectrodes.…”
Section: Stability Of Unit Recordingsmentioning
confidence: 99%
See 1 more Smart Citation